Between "La Rigenerazione" and "La coscienza di Zeno" by Italo Svevo: in Search for a New Drama Paradigm - Kaczmarek, Tomasz (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
The article proposes a new approach to Italo Svevo’s dramaturgy based on the example of his masterpiece The Regeneration, in the context of the poetics of modern and contemporary drama. Despite the matrix of the text, which seems to respect the old formal constraints, the Italian author questions certain foundations inherent in the aesthetics of the canonical form. The different strategies that go beyond the generic rules are also manifested in Zeno’s Conscience (known also in English as Confessions of Zeno), which contains some solutions of today’s theatrical aesthetics. Concluding remarks on this matter will be reserved for this work.